ChemInform Abstract: The Sequential Homobimetallic Catalysis Concept Applied to the Synthesis of Benzofuran Derivatives (Highlight). Issue 33 (19th August 2014) - Mancuso, R.; Gabriele, B.
Abstract Review: 65 refs.